Peningkatan Hasil Belajar Tematik Terpadu Siswa Menggunakan Model Take and Give di Kelas IV SDN 15 Ulu Gadut, Kota Padang - Nirmayanti Nirmayanti; Desyandri Desyandri (Universitas Negeri Padang, 2020)
This study aims to explain the success of students in integrated thematic learning using the take and give a cooperative model in grade IV SD Negeri 15 Ulu Gadut. This type of research is classroom action research. Using qualitative and quantitative approaches. The research subjects were classroom teachers as observers, researchers as practitioners, and 25 students of SD Negeri 15 Ulu Gadut. The conclusions of this study are: 1) the assessment of the percentage of the RPP got a previous increase 0f 80.55% in the first cycle and an increase of 94.44% in the second cycle. 2) teacher aspect increased 76.78% in cycle I increased 92.85% in cycle II. 3) aspect of students experienced an increase of 76.78% in the first cycle and an increase 0f 92.85% in the second cycle. 4) the conclusion of student learning has increased in the first cycle the percentage completeness is 64% to.89,12% in the second cycle.